Novel ultrasmall multifunctional nanodots for dual-modal MR/NIR-II imaging-guided photothermal therapy. (October 2020) - Li, Fenfen; Li, Tuanwei; Zhi, Debo; Xu, Pengping; Wang, Wenshen; Hu, Yi; Zhang, Yuanyuan; Wang, Shaozhen; Matula Thomas, J.; Beauchamp Norman, J.; Ding, Weiping; Yan, Lifeng; et al.
Abstract: Encouraging progress in multifunctional nanotheranostic agents that combine photothermal therapy (PTT) and different imaging modalities has been made. However, rational designed and biocompatible multifunctional agents that suitfable for in vivo application is highly desired but still challenging. In this work, we rationally designed novel ultrasmall multifunctional nanodots (FS-GdNDs) by combining the bovine serum albumin (BSA)-based gadolinium oxide nanodots (GdNDs) obtained through a biomineralization process with a small-molecule NIR-II fluorophore (FS). The as-prepared FS-GdNDs with an ultrasmall hydrodynamic diameter of 9.3 nm exhibited prominent NIR-II fluorescence properties, high longitudinal relaxivity (10.11 mM −1  s −1 ), and outstanding photothermal conversion efficiency (43.99%) and photothermal stability. In vivo studies showed that the FS-GdNDs with enhanced multifunctional characteristics diaplayed satisfactory dual-modal MR/NIR-II imaging performance with a quite low dose. The imaging-guided PTT achieved successful ablation of tumors and effectively extended the survival of mice. Cytotoxicity studies and histological assay demonstrated excellent biocompatibility of the nanodots. Importantly, this novel FS-GdNDs can undergo efficient body clearance through both hepatobiliary and renal excretion pathways. The novel ultrasmall multifunctional FS-GdNDs with excellent features hold tremendous potential in biomedical and clinical applications. Graphical abstract: Image 1